Climate finance: financial and economic considerations - Edberg, S.; Rodríguez, D.J.; Bernardini, F.; Koeppel, S.; Plotnykova, H.; Colombo, C. C.; Gaillard-Picher, D.; Gartner, T.; Amarnath, Giriraj; Hedger, M.; Kjellen, M.; Matthews, J.; et al. (2020)
This chapter addresses the current state of water and climate finance, the costs of inaction versus the benefits of action, and several ways to access climate finance flows to improve water management as well as water supply and sanitation services, while synergistically mitigating and/or adapting to climate change.